2016
DOI: 10.1093/mnras/stw3141
|View full text |Cite
|
Sign up to set email alerts
|

Gaia's view of the λ Boo star puzzle

Abstract: The evolutionary status of the chemically peculiar class of λ Boo stars has been intensely debated. It is now agreed that the λ Boo phenomenon affects A stars of all ages, from star formation to the terminal age main sequence, but the cause of the chemical peculiarity is still a puzzle. We revisit the debate of their ages and temperatures in order to shed light on the phenomenon, using the new parallaxes in Gaia Data Release 1 with existing Hipparcos parallaxes and multicolour photometry. We find that no singl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 82 publications
(92 reference statements)
3
34
0
Order By: Relevance
“…Adopting values that reproduce the observations for T Tauri stars may not be appropriate for these higher mass analogs. Second, early-type stars with metal-poor photospheres, in particular the λBoo stars, show an ultraviolet excess (Murphy & Paunzen 2017). Folsom et al (2012) and Kama et al (2015) found a relatively high fraction of HAeBes in their samples (up to ∼50%) showing the λBoo pattern to varying degrees.…”
Section: Appendix a Scattered-light Disk Samplementioning
confidence: 95%
See 1 more Smart Citation
“…Adopting values that reproduce the observations for T Tauri stars may not be appropriate for these higher mass analogs. Second, early-type stars with metal-poor photospheres, in particular the λBoo stars, show an ultraviolet excess (Murphy & Paunzen 2017). Folsom et al (2012) and Kama et al (2015) found a relatively high fraction of HAeBes in their samples (up to ∼50%) showing the λBoo pattern to varying degrees.…”
Section: Appendix a Scattered-light Disk Samplementioning
confidence: 95%
“…This is a face-on star rotating near its break-up velocity (Grady et al 2007), resulting in a significant deformation of the star and a temperature gradient from the stellar pole to the equatorial region of the star. As part of their study of λBoo stars, Murphy & Paunzen (2017) find T=6700±322K and log L å /L ☉ =0.78±0.03. We adopt these values to estimate the stellar mass and radius from the Siess et al (2000) evolutionary tracks.…”
Section: Appendix D Comment On Individual Systemsmentioning
confidence: 97%
“…Significant photospheric depletion of refractory elements, called the λ Boö phenomenon, is seen in ∼ 2 % of B to mid-F type stars (Paunzen & Gray 1997;Paunzen et al 2001;Paunzen 2001;Murphy et al 2015). The λ Boö abundance pattern is seen in young, disk-hosting stars with ages ∼ 0.1 to 10 Myr (Section 4.1) and in stars as old as 1 Gyr, on the order of their main-sequence lifetimes (Murphy & Paunzen 2017). Some λ Boö stars possess debris disks (Draper et al 2016), but the fraction of confirmed debris disks was found to be statistically indistinguishable from that in nonλ Boö sources (Gray et al 2017).…”
Section: λ Boötis Starsmentioning
confidence: 99%
“…Therefore, Yushchenko et al (2015) include HD 48497 in their list of possible λ Bootis star candidates. These stars constitute a small group of A-to Ftype stars characterized by the depletion of Fe-peak elements of up to 2 dex (Murphy & Paunzen 2017). However, HD 48497 is too hot and does not show the typical elemental abundance pattern of λ Bootis stars.…”
Section: Objectmentioning
confidence: 99%